Effective coverage of nutrition interventions across the continuum of care in Bangladesh: Insights from nationwide cross-sectional household and health facility surveys - Nguyen, Phuong Hong; Khương, Long Quỳnh; Pramanik, Priyanjana; Billah, Sk Masum; Menon, Purnima; Piwoz, Ellen; Leslie, Hannah H. (BMJ, 2021)
Improving the impact of nutrition interventions requires adequate measurement of both reach and quality of interventions, but limited evidence exists on advancing coverage measurement. We adjusted contact-based coverage estimates, taking into consideration the inputs required to deliver quality nutrition services, to calculate input-adjusted coverage of nutrition interventions across the continuum of care from pregnancy through early childhood in Bangladesh.